Clustering behaviour and settling velocity of bidisperse inertial particles in turbulent open channel flow. (August 2020) - Wang, Y.; Lam, K.M.
Highlights: The nonuniform clustering of inertial particles in turbulence is well demonstrated using Voronoï analysis. The clustering level of bidisperse inertial particles in turbulence is weaker than corresponding monodisperse inertial particles. The settling velocity of inertial particles is closely related to their local concentration. The anisotropy and large eddies in turbulence have evident influence on settling velocity of inertial particles. The contribution of unsteady term in particle dynamic equation becomes greater when turbulence intensity and/or particle inertia are smaller. Abstract: The clustering behaviour and settling velocity of bidisperse inertial particles with sub-millimetre diameters travelling in a turbulent open channel flow are investigated using the simultaneous particle image velocimetry and particle tracking velocimetry measurement technique. Instantaneous images of flow field and inertial particles are separated based on different wavelengths of light emitted by fluorescent seeding particles and inertial particles. Four flow configurations of turbulence are generated by turbulence grids with different sizes in the open channel. The clustering behaviour of monodisperse and bidisperse inertial particles and the discrepancy between them in the different flow cases are studied. We found that bidisperse inertial particles have weaker clustering phenomenon as compared with corresponding monodisperse inertial particles and this weak clustering phenomenon is almost consistent when the Taylor microscale Reynolds number Reλ changes from 90 to 267. The relationship between settling velocity and local concentration of inertial particles is then investigated. The results support the preferential concentration as the mechanism for the enhancement of settling velocimetry when the normalized particle concentration is in the range of 0.1~10. However, the anisotropy property and large eddy effect in turbulence will greatly change the interaction between inertial particles and turbulent flows and further alter their settling velocity, such as the average settling velocity decreasing with increasing Stokes number which depends on the dissipation time scale. Accordingly, we propose a new dimensionless multiscale parameter S v η R e L 1 / 2 to take into account the effect of large eddies and turbulence anisotropy on the settling velocity. With the simultaneous measurement of particle settling velocities and fluid velocities, we also analyse the unsteady force term in the particle dynamic equation. When the turbulence intensity is small and/or the particle inertia related to particle diameter and density ratio between inertial particle and fluid is small, the unsteady term can have a large contribution and it should not be neglected in the particle dynamic equation for the point-particle method in the numerical simulations of particle-laden flows.